The effects of traveling for business on customer satisfaction with hotel services. (August 2018) - Radojevic, Tijana; Stanisic, Nemanja; Stanic, Nenad; Davidson, Rob
Abstract: The purpose of this study is to examine the association between traveling for business and customer satisfaction with hotel services. To that end, a multilevel analysis is conducted of an empirical dataset comprising over 1.6 million customer reviews pertaining to 13, 410 hotels located in 80 major urban tourism destinations across the world. The results suggest that customers report significantly lower (4% on average) levels of overall satisfaction with hotel services after for-business stays than after for-pleasure stays. This effect is, moreover, found to be moderated by certain contextual factors, such as the traveler's general leisure versus work orientation, and the economic and cultural characteristics of the destination and the traveler's country of origin. Most importantly, the effect is found to be strongly moderated by certain hotel attributes; this finding allows hotel managers to offset the adverse effect by focusing on, and investing in, those attributes, making their properties more competitive. Highlights: For-business hotel service encounters are evaluated less favorably (4% on average). This effect is strongly moderated by personal-, hotel- and country-level factors. The adverse effect is smaller for more work-oriented individuals. Traveling for business is linked to intensified perception of cultural differences. Based on our results, managers can intelligently target the business segment in ads.